Masa Kerja, Postur Kerja dan Aktivitas Berulang Sebagai Determinan Musculoskeletal Disorders pada Pekerja Laundry - Munairah, Munairah; Aswin, Budi; Lanita, Usi; Perdana, Silvia Mawarti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Musculoskeletal disorders are an occupational health problem in informal sectors such as laundries, which are prone to occur due to unergonomic work postures, repetitive activities, and long work durations. The purpose of this study was to analyze the relationship between work posture, repetitive activities, length of service, and body mass index (BMI) with the incidence of musculoskeletal disorders in laundry workers. This study used a cross-sectional design, involving 82 workers selected using a proportional stratified random sampling method. Data collection was conducted using the Rapid Entire Body Assessment (REBA) worksheet, the Nordic Body Map (NBM), and questionnaires according to the variables. Data were analyzed using the Chi-square test. The analysis results showed that the p-value for each independent variable was work posture = 0.023, repetitive activities 0.029, work period 0.001, and body mass index = 0.744. Therefore, it can be concluded that the determinants of musculoskeletal disorders in laundry workers in this location are length of service, work posture, and repetitive activities.Keywords: musculoskeletal disorders; length of service; work posture; repetitive activities ABSTRAK Musculoskeletal disorders merupakan masalah kesehatan kerja pada sektor informal seperti laundry yang rentan terjadi akibat postur kerja tidak ergonomis, aktivitas berulang, dan durasi kerja yang panjang. Tujuan penelitian ini adalah menganalisis hubungan antara postur kerja, aktivitas berulang, masa kerja, dan indeks massa tubuh dengan kejadian musculoskeletal disorders pada pekerja laundry. Penelitian ini menggunakan desain cross- sectional, dengan melibatkan 82 pekerja yang dipilih menggunakan metode proporsional stratified random sampling. Pengumpulan data dilakukan dengan menggunakan Rapid Entire Body Assessment (REBA) worksheet, Nordic Body Map (NBM), dan kuesioner sesuai variabel. Data dianalisis menggunakan uji Chi-square. Hasil analisis menunjukkan bahwa nilai p untuk masing-masing variabel independen adalah postur kerja = 0,023, aktivitas berulang 0,029, masa kerja 0,001 dan indeks massa tubuh = 0,744. Dengan demikian dapat disimpulkan bahwa determinan kejadian musculoskeletal disorders pada pekerja laundry di lokus ini adalah masa kerja, postur kerja dan aktivitas berulang.Kata kunci: musculoskeletal disorders; masa kerja; postur kerja; aktivitas berulang